Previously undescribed anomalies of hepatic artery and portal venous anatomy in a case of extrahepatic biliary atresia and its implications - Prabudh Goel; Minu Bajpai; Kanika Sharma; Priyanka Naranje (Wolters Kluwer Medknow Publications, 2019)
A search on PubMed and Web of Science revealed scarcity of the literature on anomalies of hepatic artery or portal vein and the presence of arterioportal fistula in biliary atresia; although, it has long-lasting implications for both the patient and the surgeon, including hepato-pancreato-biliary surgeons, pediatric surgeons (who perform Kasai's portoenterostomy), liver transplant surgeons, and interventional radiologists. We report a case of extrahepatic biliary atresia with multiple anomalies involving the hepatic arteries, portal vein, cystic artery, arterioportal fistula and shunting, intrahepatic portal vein radicals, kidney, and external genitalia. The merits of the case from various standpoints including its implications for etiopathogenesis, caution during surgical anesthesia or postoperative management, and enrichment of the literature have been discussed.